The Development of Modern Business Supported by Local Resources for Efficiency: Utilization of Traditional Medicine - Moeljadi Moeljadi; Risna Wijayanti; Wahdiyat Moko; Suseno Haji (AIBPM Publisher, 2022)
The development of tourism after COVID-19 era begins to show positive results. One of the tourism sectors that the Indonesian Government wants to improve is village tourism. There are many potential villages in Indonesia but they are still not well developed. One of those villages is Pandansari Lor in Malang Regency. The purpose of this research is to turn this potentials into profitable businesses for the villagers. The method used in this research is exploratory qualitative. The results of this study showed that the enthusiasm of the village community to be more productive has greatly increased so in the future of the village can be a creative village. The manifestation of this creativity can later be implemented by opening cafes and culinary places that provide herbal medicine for visitors while they are enjoying the panorama. So that visitors can remember Pandansari Lor as medical village that use green environment in its process. The main goal of the project is to improve the welfare of the village community.Â Keywords: Tourism Village, Creative Village